Fluorescently tagged nanobodies and NanoBRET to study ligand-binding and agonist-induced conformational changes of full-length EGFR expressed in living cells - Comez, Dehan; Glenn, Jacqueline; Anbuhl, Stephanie M.; Heukers, Raimond; Smit, Martine J.; Hill, Stephen J.; Kilpatrick, Laura E. (Frontiers in Immunology, 2022)
The Epidermal Growth Factor Receptor is a member of the Erb receptor tyrosine kinase family. It binds several ligands including EGF, betacellulin (BTC) and TGF-α, controls cellular proliferation and invasion and is overexpressed in various cancer types. Nanobodies (VHHs) are the antigen binding fragments of heavy chain only camelid antibodies. In this paper we compared the binding characteristics of EGF-AF488, EGF-AF647 and two distinct EGFR directed fluorescent nanobodies (Q44c-HL488 and Q86c-HL488) measured using NanoBRET in living HEK293 cells. These data revealed that the EGFR nanobody Q44 is able to inhibit EGF binding to full length EGFR expressed in living cells while Q86 was able to recognise agonist bound EGFR and act as a conformational sensor. The specific binding of Q44c-HL488 and EGF-AF488 was inhibited by a range of EGF ligands (EGF> BTC>TGF-). These two nanobodies should be powerful tools for studying the role of EGFR in health and disease.